Development and validation of emission model for a petrol engine using response surface methodology (RSM) - Saidur, R.; Md Jahirul, I.; Leong, W. B.; Masjuki, H. H. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/